Resuelve los siguientes sistemas y ecuaciones

log_2(x+y)-log_2(y-7)=1

2^{x}=2^6\cdot8^{y}

 

 

 

 

 

log_{3}(x)-log_{3}(y)=3

log_{3}(2\cdot x)+log_{3}(y+6)=5+log_{3}(6)

 

 

 

 

 

 

log_{10}(x)-log_{10}(y)=2

log_{10}(4\cdot x)+log_{10}(y+7)=3+log_{10}(12)

 

 

 

 

 

 

15log3+ylog9=xlog3

xlog4-2ylog8=\frac{1}6log4096

 

 

 

 

 

 

log_{36}(x+10)^{8}-log_6\nthroot{4}{x+10}=1

 

 

 

 

 

 

log_{49}(x+10)^{10}-log_7\nthroot{4}{x+10}=1

 

 

 

 

 

 

log_{2}(x)-log_{2}(y)=1

log_{2}(4\cdot x)+log_{2}(y+3)=3+log_{2}(4)

 

 

 

 

 

 

log_{2}(x)-log_{2}(y)=3

log_{4}(4\cdot x)+log_{4}(y+127)=5+log_{4}(4)

 

 

 

 

 

 

log_{9}(x+5)^{2}-log_3\nthroot{5}{x+5}=1

 

 

 

 

 

 

log_{9}(x+14)^{6}-log_3\nthroot{7}{x+14}=1

 

 

 

 

 

 

log_{36}(x+7)^{6}-log_6\nthroot{6}{x+7}=1

 

 

 

 

 

 

log_{4}(x+7)^{2}-log_2\nthroot{7}{x+7}=1

 

 

 

 

 

 

log_{3}(x)-log_{3}(y)=1

log_{6}(3\cdot x)+log_{6}(y+11)=2+log_{6}(3)

 

 

 

 

 

 

log_6(x+y)-log_6(y-3)=1

6^{x}=6^1\cdot36^{y}

 

 

 

 

 

log_6(x+y)-log_6(y-8)=1

6^{x}=6^3\cdot216^{y}

 

 

 

 

 

log_{10}(x)-log_{10}(y)=3

log_{30}(3\cdot x)+log_{30}(y+24299)=5+log_{30}(3)

 

 

 

 

 

 

log_{10}(x)-log_{10}(y)=2

log_{10}(4\cdot x)+log_{10}(y+99)=4+log_{10}(4)

 

 

 

 

 

 

log_{36}(x+9)^{4}-log_6\nthroot{5}{x+9}=1

 

 

 

 

 

 

log_7(x+y)-log_7(y-10)=1

7^{x}=7^1\cdot49^{y}

 

 

 

 

 

log_6(x+y)-log_6(y-8)=1

6^{x}=6^2\cdot6^{y}

 

 

 

 

 

log_{49}(x+12)^{6}-log_7\nthroot{4}{x+12}=1

 

 

 

 

 

 

log_7(x+y)-log_7(y-7)=1

7^{x}=7^2\cdot343^{y}

 

 

 

 

 

16log3+ylog9=xlog3

xlog16-2ylog64=\frac{1}5log1048576

 

 

 

 

 

 

log_{36}(x+12)^{10}-log_6\nthroot{6}{x+12}=1